Counter-Literacies: o graffiti e a pixação como letramentos urbanos nas paisagens linguísticas da cidade - Giulia Soster Caminha (2021)
This transdisciplinary research stems from the studies of Critical Applied Linguistics (RAJAGOPALAN, 2004; PENNYCOOK, 2004, 2006; MOITA LOPES, 2006) and aims to investigate how language and social practice are related and how graffiti and pixação act as agents of social transformation. In addition, this research brings new notes to critical Applied Linguistics by analyzing graffiti and pixação as legitimate practices of counter literacies (PENNYCOOK, 2010) in the linguistic landscapes of the city (SHOHAMY, 2008). Furthermore, in order to enable so many crossing areas – since this research starts from critical Applied Linguistics and covers the fields of sociolinguistics (JAWORSKI; THURLOW, 2010), discourse analysis (ORLANDI, 2004) and Human Geography (SANTOS, 1984) – the method of this qualitative research is inspired by the cartographic and rhizomatic thought proposed by Deleuze and Guattari (1995). In order to raise pertinent considerations about the practices of graffiti and pixação, four artists were interviewed about their motivations and other issues involved in these modalities. Finally, to analyze the data, I have based the analysis on discourse analysis and interpretative approach, according to Denzin and Lincoln (2006).